Role of Endobronchial Ultrasound-guided Transbronchial Needle Aspiration in the Diagnosis of Bronchogenic Carcinoma - Jie SHEN; Dajiang QI; Heng ZHAO; Jian ZHANG; Baohui HAN; Jiayuan SUN; Aiqin GU (Chinese Journal of Lung Cancer, 2010)
Background and objective The aim of this study is to evaluate diagnostic yield and the safety of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) in the diagnosis of bronchogenic carcinoma. Methods Between July, 2009 and February, 2010, 95 patients with mediastinal/hilar lymphadenopathy and/or intrathoracic peritracheal or peribronchial masses previously detected with CT scan underwent EBUS-TBNA. No rapid onsite cytology was performed. Results In all 95 patients, 60 cases were newly diagnosed lung cancer through the pathological examination and clinical follow-up certification. In 60 lung cancer cases, 112 samples were obtained from lymph nodes (LNs) and 11 samples were obtained from intrapulmonary lesions. Fifty-eight cases of patients were diagnosed, false negative in 2 cases. Sensitivity and specificity of EBUS-guided TBNA method in distinguishing benign from malignant LNs or thoracic masses were 96.67% and 100%, respectively. There was any major complication in this series, the procedure was uneventful. Conclusion EBUSTBNA seemed a safe and effective technique in making bronchogenic carcinoma diagnosis for mediastinal/hilar LNs and intrapulmonary masses.